Dispersion of linear and nonlinear optical susceptibilities and the hyperpolarizability of 3-methyl-4-phenyl-5-(2-pyridyl)-1,2,4-triazole - Ali Hussain, Reshak, Prof. Dr.; Stys, D.; Auluck, S.; Kityk, I.V. (The Owner Societies, 2011)
Link to publisher's homepage at http://www.rsc.org